Effects of duration of long-acting GnRH agonist downregulation on assisted reproductive technology outcomes in patients with adenomyosis: a retrospective cohort study - Li, Yexing; Ge, Li; Yang, Xiaohe; Cui, Linlin; Chen, Zi-Jiang (Frontiers in Medicine, 2023)
Objectives: To elucidate the relationship between long-acting GnRH agonist (GnRHa) downregulation and assisted reproductive technology (ART) outcomes and identify the optimal duration of downregulation in patients with adenomyosis. Design: Retrospective cohort study. Participants: The study was designed to evaluate ART outcomes in adenomyosis patients with and without GnRHa downregulation between January 2016 and December 2020. A total of 374 patients with adenomyosis (621 cycles) were included with 281 cycles in downregulation group versus 340 cycles in non-downregulation group. After 1:1 propensity score matching (PSM) , a sample size of 272 cycles in each group was matched. The matched downregulation group was further divided into 1-month (147 cycles), 2-months (72 cycles) and ≥3 months downregulation (53 cycles) subgroups. Stratification analysis was conducted on pregnancy outcomes in 239 fresh embryo transfer (ET) cycles and 305 frozen embryo transfer (FET) cycles. Results: The downregulation group had larger mean diameter of initial uterus and higher proportion of severer dysmenorrhea compared to non-downregulation group. The pregnancy-related parameters in GnRHa downregulation group were similar to those in non-downregulation group, except for higher late miscarriage rate (MR) (13.4% vs. 3.1%, P=0.003). The subgroup comparisons in fresh ET cycles indicated that implantation rate (75.0% vs. 39.2%, P=0.002), biochemical pregnancy rate (91.7% vs. 56.0%, P=0.036) and clinical pregnancy rate (83.3% vs. 47.0%, P=0.016) could be improved by prolonged GnRHa downregulation (≥3 months), whereas late MR was difficult to be reversed (30.0% vs. 3.2%, P=0.017). In FET cycles, higher MR (53.6% vs. 29.9%, P=0.029; 58.8% vs. 29.9%, P=0.026) and lower live birth rate (18.8% vs. 34.1%, P=0.023; 17.1% vs. 34.1%, P=0.037) were observed in the 1-month and ≥3 months downregulation group, while no differences were found in the 2-months downregulation group compared to the non-downregulation group. Conclusion: In patients with severer adenomyosis, long-acting GnRHa downregulation might be correlated with improved ART outcomes. In fresh ET cycles, prolonged downregulation (≥3 months) might be beneficial to improve live birth rate, which needed to be verified by further study with larger sample. In FET cycles, the optimal duration of downregulation was not certain and still needed further exploration.